PERSEPSI BERBAGAI STRATA SOSIAL MASYARAKAT TERHADAP PASRAMAN FORMAL - Suyono Suyono (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2020)
Formal Pasraman is a religious education institution established by the community tha has been registered with a government agency. The existence of formal Pasraman is important for Hindus, because it is able to show its function of existence in accordance with the expectations of society. However, not all regions can implement these government programs, such as in Seputih Mataram Subdistrict, Central Lampun g Regency, which does not have a formal Pasraman. This research was conducted to determine the perception of the community, namely community leaders, and the general public, in Seputih Mataram Subdistrict, Central Lampung Regency, towards formal Pasraman. To abtain data ini this study used questionnaire data collection techniques. Sampling was done by using Disproportionate stratified random sampling technique using the Slovin formula. The method used in this research is descriptive quantitative percentage. The findings of the study are that the level of perception of both community leaders and the general public is not different, namely agreeing if a formal Pasraman is built in Seputih Mataram Subdistrict, except that the response in the case of formal Pasraman development within the scope of the village the level of perception of the general public is higher than community leaders. Meanwhile, the response in terms of donations of funds, material donations, and children’s interest in continuing their education at Hindu higher education, the level of perception community leaders was higher than that of the general public